2018
DOI: 10.1002/ps.4910
|View full text |Cite
|
Sign up to set email alerts
|

Cascading effects of combining synthetic herbivore‐induced plant volatiles with companion plants to manipulate natural enemies in an agro‐ecosystem

Abstract: MeSA alone or combined with coriander attracted different predator communities, altered pest communities, and reduced damage; however, these results did not cascade down to improve crop productivity. © 2018 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 77 publications
(180 reference statements)
0
19
0
4
Order By: Relevance
“…They found that natural enemies (parasitoids and predators) were more abundant near plants treated with synthetic HIPVs than near non‐treated plants, which resulted in efficient top‐down regulation of pests and reduced crop damage. Other implementations of this strategy yielded mixed success (Salamanca, Souza, & Rodriguez‐Saona, ; Simpson et al., ), highlighting the importance of optimizing the provision of companion plants and synthetic HIPVs in crop fields. Both companion plants and synthetic HIPVs may affect non‐target species.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that natural enemies (parasitoids and predators) were more abundant near plants treated with synthetic HIPVs than near non‐treated plants, which resulted in efficient top‐down regulation of pests and reduced crop damage. Other implementations of this strategy yielded mixed success (Salamanca, Souza, & Rodriguez‐Saona, ; Simpson et al., ), highlighting the importance of optimizing the provision of companion plants and synthetic HIPVs in crop fields. Both companion plants and synthetic HIPVs may affect non‐target species.…”
Section: Introductionmentioning
confidence: 99%
“…Both companion plants and synthetic HIPVs may affect non‐target species. For instance, they may attract other pests as well as non‐target natural enemies and higher trophic levels (Orre, Wratten, Jonsson, & Hale, ; Orre‐Gordon, Wratten, Jonsson, Hale, & Simpson, ; Parolin et al., ; Wäckers, Romeis, & van Rijn, ), which may in turn increase intra‐guild predation between natural enemies (Jonsson, Wratten, Landis, & Gurr, ) and fail to increase crop productivity (Salamanca et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Apart from supplying extra-floral nectars and pollen, the reward component can also offer additional benefits such as shelter and supply of alternative hosts and prey to natural enemies. The attract and reward combination significantly increases natural enemy populations in crop fields over the application of either of these components alone (Simpson et al, 2011;Salamanca et al, 2018). The combination of MeSA as attractant and buckwheat Fagopyrum esculentum Möench (Polygonaceae) as reward plant boosted the abundance of Scelonidae wasps on broccoli plants, and that of Eulophidae wasps on sweetcorn plants (Simpson et al, 2011).…”
Section: An Optimised Attract and Reward Techniquementioning
confidence: 99%
“…The combination of MeSA as attractant and buckwheat Fagopyrum esculentum Möench (Polygonaceae) as reward plant boosted the abundance of Scelonidae wasps on broccoli plants, and that of Eulophidae wasps on sweetcorn plants (Simpson et al, 2011). Salamanca et al (2018) reported that the combination of MeSA and coriander plants also led to an increased abundance of the predatory thrips Franklinotrips vespiformis (Crawford) (Thysanoptera: Aeolothripidae), predatory bugs Orius insidiosus (Say) (Hemiptera: Anthocoridae), and hoverflies, Toxomerus sp. (Diptera: Syrphidae), on bean plants, but no increase was found in the abundance of earwigs Doru sp.…”
Section: An Optimised Attract and Reward Techniquementioning
confidence: 99%
“…These compounds can also accumulate on plant surfaces and through their smell provide repellency and protection against attacking insects (Ibrahim et al 2001(Ibrahim et al , 2005Yarou et al 2017). Extracts and essential oils can be sprayed on plants or released from various dispensers (Ibrahim et al 2005;Mofikoya et al 2017;Salamanca et al 2018). Plant extracts may affect orientation behaviour or host acceptance by the herbivorous insects, but also attract some parasitoids of the pest insect (Ibrahim et al 2005;Egigu et al 2010).…”
Section: Do Svocs Deposited On Leaf Surfaces Affect Herbivorous Insects?mentioning
confidence: 99%